Fé sem grades: religião, recidivismo, liberdade de crença nos estabelecimentos prisionais e o impacto na ressocialização do preso - Arruda, Ana Patrícia Melo (2024)
The dissertation addressed the theme of the prison population in Brazil, highlighting transcendentality as a fundamental element to promote resocialization practices. The general objective is to investigate the impact on the prisoner's return to social life considering the influence of religious practices on their behavior in light of the dynamics of the prisoner's receptivity to society. Aspects about public prison policies were analyzed in a context of expression of religiosity and how they can influence the aspect of criminal law. The transcendental factor was presented as an essential issue, which goes beyond the purely secular aspect, being capable of promoting significant transformations in the life perspectives of inmates. As specific objectives, the relationship between crime, sin and resocialization as the main purpose of the administration of justice was explored. Ethical and moral aspects associated with the commission of crimes were examined, highlighting the need for an approach focused on resocialization as a way of promoting more effective and humane justice. The discussion raised questions about the nature of crime and its connection with the concept of sin, as well as the importance of understanding resocialization as a moral and social imperative. The power of belief was addressed as a crucial mechanism for the prisoner's reintegration into society, contrasting with the prevailing distrust regarding the effectiveness of the resocialization of prison inmates. The investigation sought to demonstrate how personal, spiritual or religious beliefs can play a significant role in positively transforming the lives of ex-offenders. At the same time, the challenges faced by graduates and the social distrust that often harms their opportunities for reintegration were discussed. The methodology used was bibliographic analysis on the topic, as well as specialized academic journals, finally, the analysis and insertion of recent statistical data obtained from official government channels on the proposed topic. It was concluded that an in-depth understanding of the complexity involved in the resocialization of the prison population in Brazil, highlighting the importance of transcendentality, an approach centered on resocialization and the recognition of the power of belief is an essential element to promote more effective justice and well-rounded social reintegration. -successful and that religious assistance, in addition to being a constitutional and legal imperative, can contribute positively to the return of the incarcerated person to society.